AYAT CINTA DALAM TAFSIR SUFI: (Analisis Kata Ḥubb dalam Tafsir Dzū al-Nūn al-Miṣrī) - Lilik Ummi Kaltsum (STAI AL-ANWAR SARANG, 2017)
Love is a part of human emotion in form of complete tendency toward an object. As a life guidance, the holy book of Al-Qur‟an brings to life not only the physical dimension but also the psychological dimension of humankind. Al-Qur‟an has defined one single object as the fundamental base of life namely love to the Creator of life Himself, Allah AWT. Love to God is the primary foundation which has to be built on every Muslim‟s soul. With love, worshipping feels enjoyable and with it life is both physically and mentally healthy. The problem is, why is this ideal concept not yet realized optimally in life? This writing aims at formulizing Dzu al-Nun al-Misri‟s proposition on the concept of love to Allah. Through the interpretation of verses on love, this normative concept can hopefully become a guide towards a life full of love, without violence and disunity. Key words: love, hub-mahabbah, Dzu al-Nun al-Misri